On the prediction of gas hold‐up in two‐phase flow systems using an Euler–Euler model. Issue 6 (3rd March 2020) - Mowla, Amir; Agnaou, Mehrez; Treeratanaphitak, Tanyakarn; Budman, Hector M.; Abukhdeir, Nasser M.; Ioannidis, Marios A.
Abstract: We quantify the ability of the two‐fluid Euler–Euler model to predict the overall gas hold‐up during two‐phase flow in vertical columns using a combination of experiments and simulations. Gas hold‐up in a bubble column and gas hold‐up in the less‐frequently studied co‐current flow are investigated. For homogeneous flow characterized by nearly uniform bubble size, Euler–Euler model predictions are within 10% of the experimental values for both modes of operation, if the bubble diameter supplied as input to the model is the average bubble diameter in the physical system. This also holds true for heterogeneous flow in bubble columns despite the presence of a broad distribution of bubble sizes, if turbulence and bubble swarm effects on momentum exchange between phases are properly accounted for. Swarm corrections adequate for bubble columns, are less successful for co‐current heterogeneous flow, for which gas hold‐up predictions are least accurate (average error of 22%).